Problems of Formal Review of the TNI Law: Analysis of the Principles of Public Participation and Transparency in the Formation of Legislation - Ifani, Titania Nur; Zaini, Maghfirotuz; Ohoiwutun, Y. A. Triana; Rato, Dominikus (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
Lawmaking is one of the fundamental instruments in realizing legal certainty and justice in national and state life. In practice, the legislative process in Indonesia still often sparks debate, both regarding substance and procedure. One of the prominent issues is the formation of the Indonesian National Army Law (UU TNI), which is being questioned due to alleged formal defects in its formulation stage. In this study, the type of research used is normative legal research or library research. The approaches used in this study are the statute approach, the conceptual approach, and the case approach. The main issue underlying the formal review of the TNI Law is the alleged failure to meet the principles of public participation and transparency in the legislative process, which has implications not only for the technical aspects of the law but also touches upon the dimensions of legitimacy and the quality of procedural democracy in Indonesia. Formal testing of the TNI Law within the framework of constitutional oversight of the legislative process certainly faced much debate. Out of the 10 cases submitted, all were rejected because the Constitutional Court found that the TNI Bill did not violate the law regarding its non-inclusion in the national legislation program, that the TNI Bill was a carryover, that the TNI Bill was in accordance with TNI reform, that the discussion of the TNI Law was transparent and accountable, that there was no limitation on document access or information access, and that the other 5 cases were still in the trial process.